Marine dock pilings foster diverse, native cryptobenthic fish assemblages across bioregions. Issue 17 (31st July 2017) - Brandl, Simon J.; Casey, Jordan M.; Knowlton, Nancy; Duffy, James Emmett
Abstract: Anthropogenic habitats are increasingly prevalent in coastal marine environments. Previous research on sessile epifauna suggests that artificial habitats act as a refuge for nonindigenous species, which results in highly homogenous communities across locations. However, vertebrate assemblages that live in association with artificial habitats are poorly understood. Here, we quantify the biodiversity of small, cryptic (henceforth "cryptobenthic") fishes from marine dock pilings across six locations over 35° of latitude from Maine to Panama. We also compare assemblages from dock pilings to natural habitats in the two southernmost locations (Panama and Belize). Our results suggest that the biodiversity patterns of cryptobenthic fishes from dock pilings follow a Latitudinal Diversity Gradient (LDG), with average local and regional diversity declining sharply with increasing latitude. Furthermore, a strong correlation between community composition and spatial distance suggests distinct regional assemblages of cryptobenthic fishes. Cryptobenthic fish assemblages from dock pilings in Belize and Panama were less diverse and had lower densities than nearby reef habitats. However, dock pilings harbored almost exclusively native species, including two species of conservation concern absent from nearby natural habitats. Our results suggest that, in contrast to sessile epifaunal assemblages on artificial substrates, artificial marine habitats can harbor diverse, regionally characteristic assemblages of vertebrates that follow macroecological patterns that are well documented for natural habitats. We therefore posit that, although dock pilings cannot function as a replacement for natural habitats, dock pilings may provide cost‐effective means to preserve native vertebrate biodiversity, and provide a habitat that can be relatively easily monitored to track the status and trends of fish biodiversity in highly urbanized coastal marine environments. Abstract : Few studies have investigated the biodiversity of vertebrates in artificial marine habitats across a broad geographic scale. Here, we show that marine dock pilings harbor diverse, native, and regionally characteristic assemblages of cryptobenthic fishes, which follow the latitudinal diversity gradient and include species of conservation concern such as the goby Gobiosoma spilotum and the grouper Mycteroperca bonaci. We suggest that dock pilings can serve as a refuge for native vertebrate biodiversity and posit that monitoring cryptobenthic fish assemblages from dock pilings will result in a better understanding of biodiversity trends in urbanized marine landscapes.